1992
DOI: 10.1021/je00008a021
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic dissociation constants of benzoic and nitrobenzoic acids in binary mixtures of water with acetone and tetrahydrofuran at 25.degree.C

Abstract: The dissociation constants and limiting molar conductances of benzoic and 2-, 3-, and 4nitrobenzoic acids have been determined in binary mixtures of water with acetone and tetrahydrofuran at 25 "C, respectively. The experimental data were analyzed by means of the Lee and Wheaton equation. The results are compared with those available in literature and in other water + cosolvent mixtures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…where n is the number of data points. All the symbols have been described in previous papers (10)(11)(12)(13)(14).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…where n is the number of data points. All the symbols have been described in previous papers (10)(11)(12)(13)(14).…”
Section: Resultsmentioning
confidence: 99%
“…Chloroacetic acid (from Merck, extra pure) was recrystallized from ethanol + water, dried under vacuum over P205, and stored in a desiccator. The melting point of the acid was 60-62 °C. The solvents were the same as used in previous studies, and their purification has been detailed previously (10)(11)(12)(13)(14). The fractionally distilled solvents had specific conductivities within (1-3) X 10~® S-cnr1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, many of the characteristics of electrolytes such as solubility, speciation, and activity in mixed solvents are described in terms of the solvent dielectric constant (or its inverse, 1/ε r ). A linear relationship between [Sokol et al, 2006, 2-PrOH e (2) + H 2 O (1) [Elsemongy and Fouda, 1980, f [Niazi et al, 1992] [Niazi et al, 1988] from Timmermans, 1960; DMF(2) + Ac (1) [Niazi, 1988] [Pawar and Mehrotra, 2002] h [Pawar and Mehrotra, 2002] [Awwad et al, 2002] h [Papanastasiou and Ziogas, 1992] c g is a correlation factor that characterizes the relative orientations between neighboring molecules, and K ij is a parameter determined from experimental ε r for the binary system i-j. d g is a correlation parameter and is calculated for each component, i, of the mixture by using the following equation: Kasprowicz -Kielich and Kielich, 1976;Lichtenecker, 1926;Looyenga, 1965;Mohapatra et al, 2001;Onsager, 1936;Pujari et al, 1998;Schott, 1980;Zakri et al, 1998), except for the equations suggested by Ravis et al (2004), which are based on volume changes on mixing and not volume additivity.…”
Section: Properties Of Mixed Solventsmentioning
confidence: 99%
“…Poulias and colleagues (Ritzoulis et al, 1984) studied the conductance behavior of halogen-salicylic acid (X-C 6 H 4 OHCOOH, X = 5-nitro, 5-chloro, 5-bromo, 5-fluoro and 3,5-dinitro) in MeOH + H 2 O at 25 • C (Poulias et al, 1985(Poulias et al, , 1986. Srivastava and Samant (1995) measured the dissociation constants of 2,5-dichlorobenzesulfonic acid in 20% (%w PC) PC + EC at 25 • C. Niazi et al (1993b) determined the pK of chloroacetic acid (Niazi, 1993a) and salicylic acid in binary mixtures of water and MeOH, EtOH, 1-PrOH, DMF, Ac, and AN in addition to benzoic and nitrobenzoic acids in binary Ac + H 2 O and THF + H 2 O (Niazi et al, 1992) and morin in MeOH + H 2 O (Niazi et al, 2006) at 25 • C. Recently, research work in this field seems directed toward generating more experimental data for heterocyclic organic acids and bases including 4-nitropyridine in nonaqueous solvents such as AN, MeOH, PC, and DMSO (Gurzyński et al, 2007a(Gurzyński et al, , 2007b and polycarboxilic acids in MeOH + H 2 O (Garrido et al, 2006) and AN + H 2 O (Espinosa et al, 2002). Others have measured the pK of perfluorooctanoic acid in MeOH + H 2 O at 25 • C (Burns et al, 2008) and of n-butylamine + acetic acid in AN + dioxane (Czaja et al, 2006).…”
Section: -Prohmentioning
confidence: 99%